Bible doctrine essential teachings of the Christian faith - Grudem, Wayne A. 1948-; Purswell, Jeff (Leicester, UK IVP, 1999)
includes bibliographical references and index.
Condenced from "Systematic theology" which see also.
Keywords: Theology, biblical